Pengaruh Media Visual Flash Card terhadap Hasil Belajar Peserta Didik Kelas VII SMPN 6 Dua Pitue - Sri Endang Rahayu Maspa; Muhammad Tawil; Ratnawaty Maming (Celebes Science Education, 2023)
This research aims: 1) To analyze the increase in learning outcomes of students who are taught using visual Flash Card media. 2) To analyze the increase in learning outcomes of students who are taught without using conventional media. 3) To test the learning outcomes of students who are taught to use higher Visual Flash Card Media than those taught without using Visual Flash Card Media. This research was a quasi-experimental research with a population of all grade VII students of SMPN 6 Dua Pitue consisting of 2 classes. The results showed that 1) Increased learning outcomes by using Visual Flash Card media for class VII students of SMPN 6 Dua Pitue belong to the high category with N-gain values of 0,59. 2) Increasing learning outcomes without using Visual Flash Card media for class VII students of SMPN 6 Dua Pitue in the medium category with N-gain values of 0,44. 3) Learning outcomes of students in class VII SMPN 6 Dua Pitue taught using Visual Flash Card media higher than students' learning outcomes taught without using Visual Flash Card media by thitung = 30,39 ttabel = 2,00247 so that H0 is rejected and Ha is accepted. So it can be concluded that Visual Flash Card media can use to improve students learning outcomes in abstract material such as the classification of living things.